2022
DOI: 10.1111/os.13306
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Deep Venous Thrombosis in Isolated Lower Extremity Fractures and Unsolved Problems in Guidelines: A Review of Recent Literature

Abstract: Deep venous thrombosis (DVT) has been characterized by a disorder of venous return caused by abnormal blood clotting in deep veins. It often occurs in the lower limbs and is a common complication in orthopaedics. Therefore, relevant professional organizations domestic and overseas had formulated and constantly updated relevant guidelines to prevent the occurrence of DVT. According to the management strategy of the guidelines, the incidence of DVT can be significantly reduced. However, due to the variety of fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Some studies have shown that depression remarkably affects the cognitive ability of many elderly patients with fracture complicated with cerebrovascular accident. [33][34][35] Foreign scholars have found that depression often experienced by elderly patients with fracture complicated with cerebrovascular accident will affect cognitive ability, and insecurity will coexist with depression. A high level of insecurity will also affect the ability of cognitive adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that depression remarkably affects the cognitive ability of many elderly patients with fracture complicated with cerebrovascular accident. [33][34][35] Foreign scholars have found that depression often experienced by elderly patients with fracture complicated with cerebrovascular accident will affect cognitive ability, and insecurity will coexist with depression. A high level of insecurity will also affect the ability of cognitive adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…is a prevalent complication due to traumatic fracture, which is mostly found in lower extremity fractures [5]. Previous studies have reported that the incidence of DVT in lower extremity fractures is 32% [7,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the mortality rate of patients with untreated PE is as high as 30% [3]. DVT impairs venous return due to abnormal deep vein coagulation, which usually occurs in the lower limbs and is a prevalent complication in orthopedics [4][5][6]. Previous studies have reported that fracture site, diabetes, and age are crucial factors affecting DVT occurrence in patients with lower limb fractures [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the study has shown that there is a negative correlation between psychological pain and neuropsychological performance in elderly patients with fracture complicated with cerebrovascular accident. Some studies have shown that depression remarkably affects the cognitive ability of many elderly patients with fracture complicated with cerebrovascular accident [33][34][35]. Foreign scholars have found that depression often experienced by elderly patients with fracture complicated with cerebrovascular accident will affect cognitive ability, and insecurity will coexist with depression.…”
Section: Discussionmentioning
confidence: 99%